Urban-rural disparities in acceptance of human papillomavirus vaccination among women in Can Tho, Vietnam - Tu Tran, Nguyet; Ngoc Thi Phan, Trung; Pham, Tam Thi; le, Tai Thanh; Le, Huu Minh; Nguyen, Dat Tan; Lam, Anh Nhut; Pham, Tin Trung; Le, Hieu Trung; Dang, Ngoc Bao; Tran, Kiet Chinh; Tran, Van De (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In Vietnam, cervical cancer is a significant public health concern for women. Unfortunately, despite the availability of the HPV vaccine, low vaccination rates persist.Objectives. This study investigates the discrepancy between urban and rural areas in the willingness to receive HPV vaccination with or without fees. Methods. A cross-sectional study was conducted on a sample of 648 women aged between 15 and 49, living in two urban and two rural Vietnamese districts of Can Tho, between May and December 2021.Results. The overall vaccination rate was 4%, with urban women having a higher rate of 4.9% compared to rural women at 3.1%. Among unvaccinated women, those from rural areas expressed a significantly higher desire to receive the free vaccine (91.4%) than urban women (84.4%). However, the intention to vaccinate declined when rural women and urban women were advised to pay the cost (63.4% and 57.1%, respectively). A strong correlation was found between a positive attitude and intention for vaccination, irrespective of its price or free availability. Education and access to information about the HPV vaccine were also identified as the most significant factors influencing the intention to vaccination among urban and rural women.Conclusion. The low HPV vaccination rates among women aged 15-49 living in both urban and rural regions of Vietnam are a notable public health concern. These outcomes emphasize the critical need for effective programs of vaccine laterization, as an introduction to the offer of affordable and accessible HPV vaccines for women in Can Tho, Vietnam